Effects of simulated acid rain on the pollen germination and pollen tube growth of apple (Malus sylvestris Miller cv. Golden) - Munzuroglu, O; Obek, E; Geckil, H (Akademiai Kiado, 2003)
The pollens of apple flowers have been treated with simulated acid rain solutions in range of pHs 2.9 to 5.0 in order to determine the threshold proportion values that lead the observed symptoms of detriments of acid rain. Compared to controls (pH 6.5), pollen germination decreased by 41.75% at pH 3.3 and pollen tube elongation decreased by 24.3% at pH 3.4. Acid rain threshold proportion value was around pH 3.3 and 3.4 for apple pollen germination and pollen tube elongation, respectively. Furthermore, pollen tube elongation was determined to be more sensitive to acid rain than pollen germination. The pH values below 3.1 resulted in complete destruction of pollen tubes. Pollen germination entirely stopped at around pH 3.0. Finally, it has been shown that the acid rain has a blocking effect on pollen germination and pollen tube elongation in apple. The conclusion is that not only pH value but also the quantity of acid rain is important factor in germination. The results were found statistically significant through the LSD test at levels of p < 0.05 and p < 0.01.
Keywords: acid rain; Malus sylvestris; pollen; germination; tube growth